(untitled) (Journal of Medical & Health Sciences Review, 2025)
BACKGROUND: Recto-vestibular fistula (RVF) is one of the most common forms of anorectal malformations (ARM) in female children. Primary posterior sagittal anorectoplasty (PSARP) is the preferred surgical technique; however, its outcomes may vary based on clinical and socioeconomic factors.To determine the postoperative outcomes of primary PSARP in female patients with recto-vestibular fistula presenting to a tertiary care hospital. METHODS: This descriptive study was conducted in the Department of Paediatric Surgery at Khyber Teaching Hospital, Peshawar. A total of 108 female patients with RVF who underwent primary PSARP were included. Demographic and socioeconomic data were recorded. Outcomes assessed included surgical site infection (SSI), recurrent fistula, and need for redo anoplasty. Associations between postoperative complications and patient factors (residence, maternal education, and age at surgery) were analyzed using Chi-square test, with p<0.05 considered statistically significant. RESULTS: The mean age at surgery was 6.4 ± 3.2 months (range: 2 months to 12 years), and mean body weight was 5.7 ± 1.8 kg. Most patients were from rural areas (57.4%), with 61.1% of mothers having no formal education. SSI was observed in 21 patients (19.4%), recurrent fistula in 5 (4.6%), and redo anoplasty in 2 (1.8%). The majority (74.1%) had no complications. SSI and recurrence were significantly associated with rural residence (p=0.041 and p=0.038, respectively) and maternal illiteracy (p=0.036 and p=0.047, respectively). Age at surgery (<6 months vs ≥6 months) did not show a statistically significant association with complications. CONCLUSION: Primary PSARP is an effective approach for managing RVF in female patients, with acceptable rates of complications. However, higher rates of SSI and recurrent fistula were significantly associated with rural residence and maternal illiteracy, underscoring the influence of socioeconomic disparities on surgical outcomes. Early diagnosis and better health education may improve prognosis in this population.